WEWENANG PENGADILAN PAJAK DALAM PENYELESAIAN SENGKETA PERPAJAKAN BERDASARKAN UNDANG-UNDANG NOMOR 14 TAHUN 2002 - Neti Sulistio (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT This thesis entitled "TAX COURT OF AUTHORITY IN TAX DISPUTE SETTLEMENT BY LAW NUMBER 14 OF 2002" background issue tax levied by the tax authorities (tax officials), in practice it is not uncommon cause tax disputes between taxpayers with tax authorities. Historically, settlement of tax disputes at first the authority of the Tax Advisory Council (MPP). However, these institutions are considered insufficient to resolve tax disputes, thus formed a Tax Dispute Settlement Body (BPSP) based on Law No. 17 of 1997, but in practice there is still legal uncertainty which lead to injustice. For it was published the Law of the Republic of Indonesia Number 14 of 2002 on the Tax Court in accordance with the system of judicial power in Indonesia. The purpose of this thesis is to find out how the authority of the Tax Court in a tax dispute settlement pursuant to Act No. 14 of 2002 on the Tax Court in the Tax Court, the legal efforts made in the resolution of tax disputes. The method used in this study is juridical empirical and normative. Tax dispute resolution through the Tax Court set out in Chapter IV Article 34 through Article 92 of Law No. 14 of 2002 against the verdict filed a lawsuit or an appeal.